Optimalisasi Pengelolaan Taman Prasejarah Leang- Leang Pada Kantor Dinas Pariwisata Kabupaten Maros - M Natsir Mallawi; Nurasia Natsir; muhammad Anas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The potential of tourism objects and tourist attractions in Indonesia is an invaluable gift where high biodiversity, uniqueness and authenticity of traditional culture, natural beauty, and historical and cultural heritage. This is considered to direct the management of all resources in such a way that economic, social and aesthetic needs can be met while maintaining cultural integrity, important ecological processes, biodiversity and life support systems. (Nelson, 1993:28). Ismayanti (2010: 22) says that the benefits derived from the development of the tourism industry will be felt by stakeholders consisting of local governments, the business world and the community as tourists and as hosts, each related party has roles in running the wheels of industry. The structure of the layers of the soil and the unique natural panorama are very good places to be visited by researchers, tourists and nature lovers.